2020
DOI: 10.2147/cmar.s253575
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA PSMA3-AS1 Promotes Lung Cancer Growth and Invasion via Sponging MiR-4504</p>

Abstract: Background: Long noncoding RNAs (lncRNAs) have close correlation with tumorigenesis. And how lncRNAs participate in lung cancer require investigation in-depth. The aim of this study was to determine the role of lncRNA PSMA3-AS1 in lung cancer progression. Methods: PSMA3-AS1 expression was analyzed via qRT-PCR. Kaplan-Meier method was used to analyze survival rate based on PSMA3-AS1 value. Proliferation was measured via CCK8 and colony formation assays. Transwell assay was utilized to examine migration and inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Its expression could be utilized for independently predicting patients' outcomes. Previously, Xu et al reported that circulating PSMA3-AS1 [11]. As reported in the study of Wang et al, PSMA3-AS1 expression was in correlation to stage, lymph node metastases, and OS in non-small-cell lung carcinoma [16].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Its expression could be utilized for independently predicting patients' outcomes. Previously, Xu et al reported that circulating PSMA3-AS1 [11]. As reported in the study of Wang et al, PSMA3-AS1 expression was in correlation to stage, lymph node metastases, and OS in non-small-cell lung carcinoma [16].…”
Section: Discussionmentioning
confidence: 70%
“…As reported in previous research, PSMA3-AS1 functions as an oncogenic lncRNA [9]. PSMA3-AS1 upregulation may facilitate the progress of multiple myeloma [9], esophageal cancer [10], lung cancer [11], colorectal cancer [12], and glioma [13]. Mechanically, PSMA3-AS1 accelerates lung cancer growth and invasion through sponging miR-4504 [11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…LncRNAs play a role of oncogene or tumor suppressor gene in CCA [ 18 ]. Some researches have demonstrated that PSMA3-AS1 exerted cancer-promoting function in some types of tumors [ 19 ]. Nevertheless, specific action of PSMA3-AS1 in CCA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the lncRNA PSMA3-AS1 (PSMA3 antisense RNA 1) was also upregulated in lung cancer tissues and cell lines, and was positively correlated with clinical stage and metastasis. The overexpression of PSMA3-AS1 resulted in poor prognosis of lung cancer patients, and knockdown of PSMA3-AS1 inhibited the proliferation, migration, and invasion of lung cancer cells [ 72 ].…”
Section: Reviews Of Recent Studies For Long Non-coding Rnasmentioning
confidence: 99%